Dynamics of Thought and Paradigm in Islamic Education Research with Bibliometric Analysis - Judijanto, Loso; Mokodenseho, Sabil; Tabilantang, Boby Hidayat; Podomi, Adelia (West Science Social and Humanities Studies, 2024)
This research conducts a comprehensive examination of the dynamics of thought and paradigm in Islamic education research through a mixed-methods approach, combining bibliometric analysis with qualitative content analysis. The study investigates the landscape, trends, and impact of scholarly discourse within the domain of Islamic education, aiming to elucidate patterns of publication, thematic orientations, and intellectual influences. Through bibliometric analysis, key citation metrics are presented, showcasing the significant scholarly impact and productivity within the field. Furthermore, the identification of top cited research papers provides insights into seminal contributions that have shaped the discourse on Islamic education. Visualizations such as network, overlay, and density maps offer nuanced understandings of research themes, temporal trends, and potential areas for future inquiry. This research contributes to a deeper understanding of Islamic education scholarship, offering valuable insights for scholars, policymakers, and practitioners seeking to navigate the complexities of the field and foster positive change in educational practice and policy.